Subgenomic particles in rAAV vectors result from DNA lesion/break and non-homologous end joining of vector genomes - Junping Zhang; Ping Guo; Xiangping Yu; Dylan A. Frabutt; Anh K. Lam; Patrick L. Mulcrone; Matthew Chrzanowski; Jenni Firrman; Derek Pouchnik; Nianli Sang; Yong Diao; Roland W. Herzog; et al. (Molecular Therapy: Nucleic Acids, 2022)
Recombinant adeno-associated virus (rAAV) vectors have been developed for therapeutic treatment of genetic diseases. Current rAAV vectors administered to affected individuals often contain vector DNA-related contaminants. Here we present a thorough molecular analysis of the configuration of non-standard AAV genomes generated during rAAV production using single-molecule sequencing. In addition to the sub-vector genomic-size particles containing incomplete AAV genomes, our results showed that rAAV preparations were contaminated with multiple categories of subgenomic particles with a snapback genome (SBG) configuration or a vector genome with deletions. Through CRISPR and nuclease-based modeling in tissue culture cells, we identified that a potential mechanism leading to formation of non-canonical genome particles occurred through non-homologous end joining of fragmented vector genomes caused by genome lesions or DNA breaks present in the host cells. The results of this study advance our understanding of AAV vectors and provide new clues for improving vector efficiency and safety profiles for use in human gene therapy.